Profiling oral health status, values, and related quality of life in patients with oral cancer: a pilot study - Rodrigues, Inês; Botelho, João; Machado, Vanessa; Proença, Luís; Mendes, José João; Zagalo, Carlos (Frontiers in Oral Health, 2023)
Patients suffering from oral cancer often do present higher odds towards common dental conditions, lower dental health literacy and related quality of life, yet poorly is known on the impact of oral health values in these patients. This study aims to explore the oral health status and their oral health determinants and reported outcomes in patients with oral squamous cell carcinoma (OSCC), at the Instituto Português de Oncologia de Lisboa Francisco Gentil (IPOLFG). This cross-sectional study included patients with a first diagnosis of OSCC that completed a questionnaire including sociodemographic data, oral health value scale (OHVS), the short-form oral health impact profile (OHIP-14), self-report periodontitis and caries experience through the decay-missing-filled index. The final sample consisted of 46 OSCC patients with 34 males and 12 females, and an average age of 70.0 years (± 13.2), most of them retired (65.2%). There was no differences between sex regarding age (p=0.531), employment status (p=0.114), presence of systemic conditions, smoking habits (p=0.423) or alcohol consumption (p=0.404). In the OHVS, there was a statistically significant difference between men and women regarding the retention of natural teeth (p=0.021). Self-perceived periodontitis had worse functional limitation (p=0.039) and physical pain (p=0.049). Regarding caries experience, patients had more posterior teeth absent (59.2%). This sample presented considerable high deterioration of oral health other than the diagnosed OSCC. The oral health value and quality of life was severely declined. There is a concerning lack of oral care and health that, consequently, impacts the quality of life of these patients